Plant Growth Regulators in Water Stress Tolerance - G S R Murti; K K Upreti (Journal of Horticultural Sciences, 2007)
The present review provides an insight into the relationship between plant growth regulators and water stress with emphasis on metabolic events that regulate growth regulator balance and physiological responses. Possible mechanisms by which ABA controls stomatal function and growth under stress, and interacts with proteins and important osmo-protectants, have been discussed. ABA involvement in signal transduction and root-shoot communication through its effects on gene and gene products is also included. A brief description of involvement of other growth regulators such as cytokinins, ethylene, polyamines and brasssinosteroids in water stress tolerance is also provided. Salient achievements in exploiting the potential of growth regulators in the resistance to water stress in some horticultural crops are also given. Gaps in existing information on plant growth regulator research in water stress tolerance have been summarized.